Touring Vilna: Images of the City and its Jews in Guidebooks and Travelogues, 1856–1939 - Kuznitz, Cecile E. (Colloquia, 2021)
From the mid-19th century through the end of the interwar period, a variety of texts about Vilna were published to guide and inform both tourists and armchair travellers. The Polish, French and German language guidebooks and travelogues considered in this article were composed both by native sons and visitors who wished to share their impressions of the city, its notable sights, and its residents. While some overlooked the presence of Jews, most devoted some space to Vilna’s Jewish landmarks. Overwhelmingly, they focused their attention on the Jewish quarter, the traditional heart of Jewish life, although a minority ventured to newer neighbourhoods, where they discovered a vibrant modern community. Their attitudes included a mix of sympathy, fascination and revulsion; many employed the language of orientalism, even as they invested that language with a variety of meanings. These authors’ narratives were shaped by their views of the various groups that comprised Vilna’s diverse population, as well as by commitments ranging from Polish nationalism to pacifism. Such accounts thus illuminate competing visions of the larger society and the place of Jews within it